Pinpointing the short-tandem repeats alleles for ethnic inferencing in forensic identification by K-medoids approach - Yoni Fuadah Syukriani; Yuyun Hidayat (Wolters Kluwer Medknow Publications, 2023)
Background: The role of DNA analysis for ethnicity inferencing is a topic that attracts much interest from researchers in forensic identification, especially for identifying unknown bodies and trace evidence. So far, the approaches considered effective for ethnic inferencing are autosomal single-nucleotide polymorphisms, Y-chromosome short-tandem repeats (STRs), and mitochondrial DNA haplotyping, which successfully demonstrates the association of specific nucleotides or patterns with population groups. Ethnic inferencing based on autosomal STRs is complex due to the nature of recombination in gamete formation. Aim: This study attempts to use clustering analysis to associate alleles and loci of autosomal STRs with population groups. Materials and Methods: We examined the allele frequency data from 19 STRs loci from the Malay Indonesian population (n = 470) to compare with other populations, namely, Chinese Indonesian (n = 133) and four reference populations (Malay Malaysian, Filipino, Chinese, and Caucasian). K-Medoids clustering analysis was carried out to pinpoint alleles and loci affecting the population clustering process. Results: The first stage of clustering results placed Malay Indonesians and four other Asian populations, namely, Chinese Indonesian, Malay Malaysian, Filipino, and Chinese, in Cluster 1, whereas the Caucasian group was in Cluster 2. It indicates that the CSF1PO, D5S818, and D8S1179 loci significantly distinguished the five Asian population groups from the Caucasian group, whereas D2S441, D8S1179, and D22S1045 were the three loci that significantly influenced the separation between Malay Indonesians and other groups. Conclusions: We conclude that K-medoids clustering analysis has the potential to play a role in ethnicity estimation by pinpointing specific STRs alleles.